2020
DOI: 10.1039/c9nr08076g
|View full text |Cite
|
Sign up to set email alerts
|

An unexpected surfactant role of immiscible nitrogen in the structural development of silver nanoparticles: an experimental and numerical investigation

Abstract: N-Surfactant-facilitated sputter deposition provides strong selectivity for crystalline orientation and facets due to drastic decreases in the surface free energies of Ag nanoparticles supported on oxide substrates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 41 publications
3
18
0
Order By: Relevance
“…However, O2 causes increase of the Ag-layer electrical resistivity, relative to films grown in pure Ar atmosphere, unless the surfactant gas is only deployed during the initial stages of island nucleation, growth and coalescence. The overall results are consistent with previous findings on the effect of N2 on Ag-layer growth on SiO2 42,43 ; yet significantly smaller amounts of O2 are required to affect morphology owing to its higher reactivity toward Ag compared to that of N2. The knowledge generated herein provides critical insights for the development of non-invasive growth manipulation strategies in which 2D morphology can be promoted by deploying gaseous species, as well as other less-noblemetals, at the film growth with high temporal precision to target and selectively modify critical film formation stages.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…However, O2 causes increase of the Ag-layer electrical resistivity, relative to films grown in pure Ar atmosphere, unless the surfactant gas is only deployed during the initial stages of island nucleation, growth and coalescence. The overall results are consistent with previous findings on the effect of N2 on Ag-layer growth on SiO2 42,43 ; yet significantly smaller amounts of O2 are required to affect morphology owing to its higher reactivity toward Ag compared to that of N2. The knowledge generated herein provides critical insights for the development of non-invasive growth manipulation strategies in which 2D morphology can be promoted by deploying gaseous species, as well as other less-noblemetals, at the film growth with high temporal precision to target and selectively modify critical film formation stages.…”
Section: Discussionsupporting
confidence: 91%
“…We use in situ and real-time spectroscopic ellipsometry to monitor the evolution of optoelectronic properties of electricallyconductive layers and, in combination with ex situ microstructural analysis, we establish that presence of O2 throughout all film-formation stages, leads to a more pronounced 2D morphology, smoother film surfaces, but larger continuous-layer electrical resistivities, relative to Ag films grown in a pure argon (Ar) atmosphere. These trends are qualitatively consistent with the effect of N2 on Ag-layer morphology 42,43 . However, a ~10 times smaller O2 partial pressure is required for the surfactant effect to manifest itself; which can be explained by the higher reactivity of O2 toward Ag, as compared to that of N2 [44][45][46] .…”
Section: Introductionsupporting
confidence: 85%
“…On the basis of these studies, we conclude that the presence of N 2 in the gas atmosphere causes suppression of coalescence-induced cluster reshaping, promoting in-plane island growth and 2D growth morphology. In a recent study of vapor-based growth of Ag nanoparticles on ZnO in Ar/N 2 gas mixtures, Yun et al 44 suggested that atomic nitrogen incorporation onto nanoparticle facets lowers their surface energy and thereby the thermodynamic driving force for coalescence. This mechanism may also be relevant for explaining the results in Figure 2, but further research is required to understand the atomistic pathways by which N 2 suppresses the coalescence rate of nanoscale Ag islands.…”
Section: Resultsmentioning
confidence: 99%
“…The mechanisms that govern morphological evolution of metal films on weakly interacting substrates are different than those in strongly interacting homo- and heteroepitaxial systems. , As a result, established knowledge for surfactant-based growth manipulation is not directly applicable to the case of noble-metal-film deposition on, e.g., oxides and 2D materials. Despite this, empirical studies exist in which less-noble-metal surfactants and seed layers as well as gaseous surfactants (nitrogen (N 2 ) and oxygen (O 2 )) have been used to suppress 3D morphology of silver (Ag) and copper (Cu) films on oxide substrates. The presence of surfactants at the film growth front, however, is often accompanied by changes in other physical properties of the noble-metal layers (e.g., electronic, optical, and transport properties), ,, which, if not reversed or mitigated, render surfactant-based approaches largely inapplicable for metal-contact synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…[3,5,7,73] Growth manipulation by surfactants is less well studied in these systems, however, empirical studies show that surfactants can suppress the uncontrolled formation of a 3D morphology, e.g., oxygen and nitrogen increase the island nucleation density, and improve wetting of Ag and Cu films on oxide substrates, promoting a 2D film morphology. [74][75][76][77][78][79][80]…”
Section: Minority Speciesmentioning
confidence: 99%